Growth and yield of chilli (Capsicum annuum L.) in response to mulching and potassium fertilization - R. Zainal Abidin (2023)
Afield experiment was conducted to study the influence of levels of potassium fertilizer (0, 66 and 132 kg ha1 ) and types of mulching (black plastic, reflective plastic and coconut fronds) on growth and yield of chilli Plant height, yield, fruit number and dry weight of plant increased with increasing K levels and mulching. Yields were increased by 89% and 142% with K levels of66 and 132 kg ha1 , respectively. Highest yield was obtained from plant grown under reflective plastic mulch. Nitrogen, P, K and Ca content in leaf tissues, soil temperature and moisture under mulched conditions were higher than without mulch. There was a positive correlation between plant dry weight with soil temperature and moisture.